Identity as a Manifestation of the Wholeness of Personality - N.V. Grishina (Социальная психология и общество)
Objective. Consideration of the phenomenon of identity in the context of integrity as a fundamental characteristic of personality; discussion of the thesis on the possibility of understanding identity as a manifestation of personality wholeness. Background. The consequence of the transition from structural descriptions of personality with an emphasis on its stable characteristics to processual-dynamic descriptions, characteristic of modern personality psychology, is an increased attention to the fundamental properties of personality and a revision of a number of traditional views about personal phenomenology. These fundamental properties include the wholeness of the personality. The development of approaches to the study of wholeness is the most important task of psychology, since it is the "separation" of personality into separate mental formations that is considered one of the main causes of the methodological crisis of psychology of the twentieth century. The description of the wholeness of the personality can be carried out by analyzing personal phenomena that are manifestations of the wholeness of the personality. It is proposed to consider personality identity as the main manifestation of personality wholeness in personal phenomenology. Methodology. A system approach to personality, methodological principles of the processual approach. Conclusions. In modern psychology, the concepts of personal wholeness and identity lose their structural certainty and are considered as dynamic formations. Recognition of its contextual nature is essential for the study of identity. In interaction with the context, identity performs the function of "gathering" a personality, ensuring its integrity.